Sensing materiality's rhetorical force: building a deeper understanding of the rhetorical entanglements of materiality, embodiment, and power - McCreary, Miranda L., author; Dickinson, Greg, advisor; Anderson, Karrin Vasby, committee member; Burgchardt, Carl, committee member; Chatterjee, Sushmita, committee member (Colorado State University. Libraries, 2025)
In this dissertation, I examine the complex relationship among the rhetorical nature of materiality, embodiment, and power. To do this, I undertake embodied rhetorical analyses of two spaces—a Walmart Supercenter and a Regal Nail Salon—and explore the various ways in which these elements intertwine to structures spaces for the emergence of the Agentic Hand, Hand as Feminized Object, and the Subversive Agentic Hand. In order to more fully understand the ways that these spaces (what I refer to as sensory architectures, composed of circulations of matter-energy co-constituting the space of which humans are a part), structure these emergences, I develop two conceptual contributions: an expanded definition of rhetoric's materiality and an understanding of rhetoric as kinaesthetic. My first conceptual contribution, an expanded definition of rhetoric's materiality, describes rhetoric's materiality as the suasory, mercurial movements of matter-energy, with two distinct characteristics: (1) matter-energy moves in dynamic, lively ways, and our embodied experience and understanding of these suasory movements is made possible through affect, and (2) the suasory movements of matter-energy are always influenced by directional lineages of power, but never predetermined by them. My second conceptual contribution, an understanding of rhetoric as kinaesthetic, explains how the rhetorical, suasory force of materiality evokes presence effects that are both relational and kinaesthetic, where kinaesthetic presence effects refer to particular senses of one's own embodiment at any point in time. Ultimately, I argue that these two conceptual contributions offer valuable tools for better understanding the relationships among rhetoric's materiality, embodiment, and power. I believe that they are uniquely useful for two primary reasons: (1) because my expanded definition of materiality is more attuned to the fundamental role of power in materiality than many other conceptual definitions, and (2) because my understanding of rhetoric as kinaesthetic expands current understandings of rhetoric's presence effects to include both relational and kinaesthetic effects. For these reasons, I believe that the two conceptual contributions I offer in this dissertation can serve as important analytical tools for continuing the collective scholarly journey to more deeply understand the entanglements of rhetoric's material force, embodiment, and power.